PENGEMBANGAN MODUL PEMBELAJARAN BLENDED LEARNING BERBASIS WEB CENTRIC COURSE MOODLE PADA MATERI KOLOID DI KELAS XI SMA - Widi Yanto (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2018)
This type of research is the development research. Model and procedures development using 4-D model comprising the steps define, design, develop, and disseminate. In the define phase, analysis of curriculum and analysis of learner are done, the design phase is to design learning modules blended learning web-based centric course Moodle. At the stage of develop, validated by linguists, design experts, media specialists and subject matter experts and trial limited to SMAN 2 Pangkalan Kerinci, to determine the validity, practicalities and the effectiveness of learning modules blended learning web-based centric course moodle developed, phase disseminate is not done. Data obtained to determine the validity of the learning modules blended learning web-based centric course Moodle derived from the questionnaire validation. The data that is used to determine the practicalities of the questionnaire obtained from the practicalities of professors, teachers, and learners. Efficacy data is obtained from the output of study of the students. The results show that the development of learning modules for blended learning web-centric based on the Moodle course colloidal material in class XI mathematics specialization natural sciences by linguists very valid (90.59%) with excellent language quality, design experts very valid (89.66%) with quality excellent design, excellent media experts (91.00%) with excellent quality media, and subject matter experts very valid (91.78%) with excellent quality material. Practicalities modules for lecturers very practical to the average of all aspects of 98.67%. Results of research by implementing the module in the learning active learners showed 90.24% of the study of students with an average of 93.24 and 100% classical completeness. It can be concluded blended learning modules web-based centric course Moodle on colloidal material proved effective. Keywords : Pengembangan, Modul Blended Learning, Web Centric Course, Moodle, Koloid